Frontispiece: Enantioselective Synthesis of Chiral Isotopomers of 1‐Alkanols by a ZACA–Cu‐Catalyzed Cross‐Coupling Protocol. Issue 49 (1st December 2014) - Xu, Shiqing; Oda, Akimichi; Negishi, Ei‐ichi
<x xml:space="preserve">Abstract</x> Chiral Isotopomers Chiral compounds arising from the replacement of hydrogen (H) by deuterium (D) are very important in the fields of organic chemistry and biochemistry. Due to the very small differences between the isotopes, it is still very challenging to synthesize chiral isotopomers in high enantiomeric purity. In their Communication on page 16060 ff., E.‐i. Negishi et al. report a widely applicable and catalytic method for the synthesis of various β‐ and more‐remotely chiral 1‐alkanols of isotopic cryptochirality (specific rotation is non‐measurable) in high enantiomeric purity (≥99% ee) through a Zr‐catalyzed asymmetric carboalumination of alkenes (ZACA reaction)/Cu‐catalyzed cross‐coupling protocol.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>